ESTIMATING THE DEMAND FOR RAILWAY FREIGHT TRANSPORTATION: A CASE STUDY IN KAZAKHSTAN - Madiyar SULTANBEK; Nazdana ADILOVA; Aleksander SŁADKOWSKI; Arnur KARIBAYEV (Transport Problems)
This article focuses on the critical importance of demand estimates for effective planning and decision-making in the railway freight transportation industry. Various departments within transportation companies, including marketing, production, distribution, and finance departments, heavily rely on accurate demand forecasts to make informed decisions. Forecasting demand is a crucial aspect of managing business processes, and the methods for doing this can vary across different industries. The ultimate goal remains consistent—to obtain precise predictions of future demand by analyzing historical data and current environmental factors. In the context of transportation services, accurate demand forecasting is essential for successful operational planning and management of functional areas such as transportation operations, marketing, and finance. The current case study specifically examines the National Company Kazakhstan Temir Zholy (KTZ), a transport and logistics holding engaged in rail transportation in Kazakhstan. KTZ’s main sources of income are related to freight transportation. The volume of cargo transportation (in tons) and the freight turnover play a significant role in assessing demand and forecasting future revenues from freight traffic. Different techniques for demand forecasting are explored, including qualitative and quantitative methods. Qualitative methods rely on judgments and opinions, while quantitative methods utilize historical data or identify causal relationships between variables. Overall, the present study highlights the critical role of demand forecasting in the railway freight transportation industry and its impact on efficient planning and decision-making processes.